INCREASING STUDENTS’ LISTENING SKILL USING RECORDED CNN NEWS AT ELEVENTH GRADE OF SMA NEGERI 18 MAKASSAR - Anita Wulandari; Hj. St. Haliah Batau; Ulfah Syam (Lembaga Jurnal FKIP Universitas Bosowa, 2022)
This study aimed to know whether the use of Recorded CNN News as Learning Media can or not increase Students’ Listening Skill at eleventh grade of SMA Negeri 18 Makassar. This study used a pre-experimental research method in one class pre-test and post-test. The population of this research was the eleventh-grade students of SMAN 18 Makassar in the 2021/2022 academic year. The samples was numbered 20 students from class XI IPS 1. The data were obtained from the listening test. The results of the study using inferential analysis of t-test by SPSS v.16 application. After analyzing data, the writer concluded that using of Recorded CNN News as learning media can increase students’ listening skill. It can be proved by the average score based on students’ pre-test and post-test. The mean score of the students’ listening increased from 39.90 in pre-test to 83.30 in the post-test. This fact shows that the hypothesis H₁ is accepted and of course the hypothesis H₀ is rejected. It’s mean that Recorded CNN News can increase students’ listening skill at eleventh grade of SMA Negeri 18 Makassar.